Effects of Coronavirus and Pneumonia on Pregnancy and Fetal Status - Komilova, Mehrinoz Oybekjon qizi; Zufarova, Shahnoza Alimjanovna; Yuldasheva, Azada Sobirovna (Journal of Science in Medicine and Life, 2024)
One of the most common complications in pregnant women infected with COVID-19 is the development of pneumonia. Taking into account that the supply of oxygen to the fetus directly depends on the level of oxygen in the mother's blood, respiratory failure often caused by the pathology of the respiratory system leads to hypoxia of the fetus. Also, the effect of the virus on the fetus is different and can often cause the development of pathological conditions. And since the treatment is carried out by prescribing antibiotics, the effectiveness of the therapy can be achieved at the cost of harming the health of the unborn child. Therefore, as a solution to this problem, it is necessary to thoroughly study the complications of new corobavirus infection in pregnancy, develop preventive and rehabilitation measures.